2021
DOI: 10.1002/wmh3.469
|View full text |Cite
|
Sign up to set email alerts
|

Access to genetic testing for rare diseases: Existing gaps in public‐facing information

Abstract: Genetic testing plays an increasingly important role in the diagnosis and potential treatment of inherited and rare conditions, such as aniridia—a disease that leads to abnormal eye development, as well as in health research on these conditions. As genetic testing is increasingly sought for accurate and early diagnosis of rare genetic disorders and in the context of direct‐to‐consumer genomics, it is critical to examine the public‐facing information about access to these services and reimbursement policies. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Projects such as the 100,000 Genomes Project in the UK led to a local increase of genetic tests (22-24). In other countries, availability of genetic testing is still limited for PCD diagnostics and rare diseases in general (25, 26). In many countries, structural changes in healthcare systems would be needed to improve access to genetic testing, which is a slow process that unfortunately limits care and equal opportunities for patients with rare diseases worldwide (27).…”
Section: Discussionmentioning
confidence: 99%
“…Projects such as the 100,000 Genomes Project in the UK led to a local increase of genetic tests (22-24). In other countries, availability of genetic testing is still limited for PCD diagnostics and rare diseases in general (25, 26). In many countries, structural changes in healthcare systems would be needed to improve access to genetic testing, which is a slow process that unfortunately limits care and equal opportunities for patients with rare diseases worldwide (27).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly in an Australian discrete choice experiment study, participants reported a reluctance to genetic testing when presented with higher costs and requirement to disclose results to health insurers (Goranitis et al 2020 ). It is important to account for the geographical location of patients, as the costs and insurance coverage can vary (Robillard et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, given the retrospective nature of this study, there was no consistency in genetic evaluation; most patients had undergone targeted sequencing of PAX6, especially patients who underwent initial evaluation several decades ago. It is possible that mutations in other genes associated with anterior segment dysgeneses may have been missed, although this is becoming less common with recent advancements in whole exome sequencing [ 42 ].…”
Section: Discussionmentioning
confidence: 99%